Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which ordered pair is a solution to the given system of linear equations, we need to check each pair against both equations. The system of equations is:
1. [tex]\( x + 2y = 3 \)[/tex]
2. [tex]\( y = -2x - 3 \)[/tex]
Let's examine each given ordered pair to see which one satisfies both equations:
### Pair (-3, -3)
1. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = -3 \)[/tex] into the first equation:
[tex]\[ -3 + 2(-3) = -3 - 6 = -9 \neq 3 \][/tex]
Therefore, (-3, -3) does not satisfy the first equation.
### Pair (3, 3)
1. Substitute [tex]\( x = 3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first equation:
[tex]\[ 3 + 2(3) = 3 + 6 = 9 \neq 3 \][/tex]
Therefore, (3, 3) does not satisfy the first equation.
### Pair (3, -3)
1. Substitute [tex]\( x = 3 \)[/tex] and [tex]\( y = -3 \)[/tex] into the first equation:
[tex]\[ 3 + 2(-3) = 3 - 6 = -3 \neq 3 \][/tex]
Therefore, (3, -3) does not satisfy the first equation.
### Pair (-3, 3)
1. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first equation:
[tex]\[ -3 + 2(3) = -3 + 6 = 3 \][/tex]
The first equation is satisfied.
2. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the second equation:
[tex]\[ y = -2(-3) - 3 = 6 - 3 = 3 \][/tex]
The second equation is also satisfied.
Since the ordered pair [tex]\((-3, 3)\)[/tex] satisfies both equations in the system, it is the solution to the system. Therefore, the correct ordered pair is:
[tex]\[ (-3, 3) \][/tex]
1. [tex]\( x + 2y = 3 \)[/tex]
2. [tex]\( y = -2x - 3 \)[/tex]
Let's examine each given ordered pair to see which one satisfies both equations:
### Pair (-3, -3)
1. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = -3 \)[/tex] into the first equation:
[tex]\[ -3 + 2(-3) = -3 - 6 = -9 \neq 3 \][/tex]
Therefore, (-3, -3) does not satisfy the first equation.
### Pair (3, 3)
1. Substitute [tex]\( x = 3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first equation:
[tex]\[ 3 + 2(3) = 3 + 6 = 9 \neq 3 \][/tex]
Therefore, (3, 3) does not satisfy the first equation.
### Pair (3, -3)
1. Substitute [tex]\( x = 3 \)[/tex] and [tex]\( y = -3 \)[/tex] into the first equation:
[tex]\[ 3 + 2(-3) = 3 - 6 = -3 \neq 3 \][/tex]
Therefore, (3, -3) does not satisfy the first equation.
### Pair (-3, 3)
1. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first equation:
[tex]\[ -3 + 2(3) = -3 + 6 = 3 \][/tex]
The first equation is satisfied.
2. Substitute [tex]\( x = -3 \)[/tex] and [tex]\( y = 3 \)[/tex] into the second equation:
[tex]\[ y = -2(-3) - 3 = 6 - 3 = 3 \][/tex]
The second equation is also satisfied.
Since the ordered pair [tex]\((-3, 3)\)[/tex] satisfies both equations in the system, it is the solution to the system. Therefore, the correct ordered pair is:
[tex]\[ (-3, 3) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.